THE ROLE OF WOMEN IN NAVOI'S LITERARY UNIVERSE A REFLECTION OF TIMURID SOCIETY AND IDEALS - Rakhmonova Shakhlo Rashidovna (Journal of Language and Literature Education, 2025)
Alisher Navoi, a seminal figure of the Timurid Renaissance, offers a literary universe where women play a critical role in reflecting and shaping societal and philosophical ideals. Rooted in the rich cultural and intellectual milieu of the Timurid Empire, Navoi’s works intertwine themes of virtue, wisdom, and spiritual transcendence with intricate depictions of female characters. This study employs a multidisciplinary approach, including literary analysis, historical contextualization, and philosophical inquiry, to examine Navoi’s portrayal of women. The objectives of this research are to explore the dual narrative of empowerment and limitation faced by women in Navoi’s literary works, assess how these portrayals align with Timurid cultural ideals, and analyze their symbolic significance within Sufi philosophy. The research findings reveal that women in Navoi’s narratives serve as both literary ideals and reflections of historical realities. The results suggest that while Navoi’s depiction of women is progressive in certain aspects, it remains confined within the patriarchal structures of his time. This study contributes to a broader understanding of gender roles and cultural identity in the Timurid Renaissance.   Keywords: Alisher Navoi, Timurid Renaissance, Gender Dynamics, Sufism, Female Empowerment